Persistence of the midline septum of the odontoid process: anatomical and radiological study - Iwanaga, Joe; Samrid, Rarinthorn; Kitagawa, Norio; Ishak, Basem; Uchikado, Hisaaki; Keshavarzi, Sassan; Maulucci, Christopher M.; Dumont, Aaron S.; Tubbs, R. Shane (Surgical and radiologic anatomy. [Englische Ausgabe], 2025)
During our screening of the computed tomography (CT) images of the craniocervical junction, we noticed that the odontoid process occasionally contains a highly ossified region in the midline consistent with a bony septum. Given its potential significance, this study aimed to investigate the highly ossified region in the midline of the odontoid process and to discuss its clinical relevance.